2019
DOI: 10.1111/jasp.12637
|View full text |Cite
|
Sign up to set email alerts
|

Self‐regulated studying behavior, and the social norms that influence it

Abstract: Teachers use injunctive norms when telling students what they should be doing. But researchers find that sometimes descriptive norms, information about what others are doing, more powerfully influence behavior. Currently, we examine which norm is more effective at increasing self-regulated studying and performance in an online college course. We found injunctive norms increased study behaviors aimed at fulfilling course requirements (completion of assigned activities), but did not improve learning outcomes. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…According to Eyink et al (2019), the positive relationship between subjective norms and intention exists because societal pressure and the intrinsic need to fit in have an impact on individual behaviour. This could be because Malaysian cultures are more concerned with what others think of them because they are collectivistic rather than individualistic (Hofstede Insights, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…According to Eyink et al (2019), the positive relationship between subjective norms and intention exists because societal pressure and the intrinsic need to fit in have an impact on individual behaviour. This could be because Malaysian cultures are more concerned with what others think of them because they are collectivistic rather than individualistic (Hofstede Insights, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Smyth and colleagues have studied the influence of norms in university education (Smyth, Chandra, & Mavor, 2018;Smyth, Mavor, & Platow, 2017;Smyth, Mavor, Platow, Grace, & Reynolds, 2015), showing that perceived learning norms of peers and educators affect student learning behaviours: if students believe that their peers and educators favour learning for understanding rather than just memorising, they are more likely to engage in learning for understanding themselves. Similarly, sending students a normative message where staff recommended spending more time on lesson activities (versus a control message) led to an increase in the amount of time spent on lesson activities and to a higher quiz score (Eyink et al, 2020). To our knowledge, there is no literature about the social norms surrounding the use of lecture recordings, and bridging this gap is one of the key aims of this study.…”
Section: Social Normsmentioning
confidence: 96%
“…For example, Huang et al (2021) showed that presenting information about peers' on-time assignment completion positively influenced learners' on-time assignment submission rate. Eyink et al (2020) reported that displaying other students' learning activities made learners do more practice before exams. Table 1 summarises the studies on peer influence in online learning contexts.…”
Section: Peer Influence In Online Learningmentioning
confidence: 99%